PROSPECTIVE ANALYSIS OF THE EFFECT OF CHRONIC STRESS ON GLYCEMIC VARIABILITY IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Dr Pinank Mer (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
Background:Chronic psychological stress is increasingly recognized as a significant factor influencing glycemic control in individuals with Type 2 Diabetes Mellitus (T2DM). Stress may contribute to glycemic variability (GV) through its effects on hormonal regulation and behavioral patterns. This study aimed to prospectively evaluate the relationship between chronic stress and GV in patients with T2DM.Materials and Methods:A total of 120 patients diagnosed with T2DM were enrolled in a 6-month prospective observational study. Participants were evaluated for chronic stress using the Perceived Stress Scale (PSS-10) at baseline and at 3-month intervals. Glycemic variability was assessed through continuous glucose monitoring (CGM) parameters, including standard deviation (SD), coefficient of variation (CV), and mean amplitude of glycemic excursions (MAGE). Data were analyzed using Pearson correlation and multivariate regression to identify associations between stress levels and GV indices.Results:Patients with high chronic stress (PSS ≥ 20) showed significantly increased GV parameters compared to those with lower stress levels. The mean SD of glucose readings in the high-stress group was 54.8 ± 11.3 mg/dL versus 42.7 ± 9.5 mg/dL in the low-stress group (p < 0.001). Similarly, MAGE was elevated in the high-stress group (102.3 ± 18.7 mg/dL) compared to the low-stress group (85.6 ± 15.2 mg/dL; p = 0.002). A positive correlation (r = 0.62, p < 0.001) was observed between PSS scores and GV metrics. Multivariate regression confirmed chronic stress as an independent predictor of increased GV.Conclusion:Chronic stress significantly contributes to increased glycemic variability in patients with T2DM, independent of HbA1c levels and medication adherence. Routine assessment and management of psychological stress may play a crucial role in optimizing glycemic outcomes in diabetic care.